Orphans, Converts, and Prostitutes: Social Consequences of War and Persecution in the Ottoman Empire, 1914–1923 - Üngör, Uǧur Ümit (War in History, 2012)
Considerable research has been conducted on the relationship between the First World War and the persecutions of Ottoman Armenians. So far, little is known about the aftermath of the catastrophe, in particular the fate of the survivors, mostly women and children who continued to live as best as they could on the fringes of society. This article addresses this hiatus and discusses the experience of Armenian survivors. It analyses the impact of the war and the genocide on Armenian women and children during and after the war. It examines how the violence generated innumerable orphans, and how these orphans became a battleground between Turkish and Armenian political elites. It reviews how the Young Turk regime dealt with the unforeseen phenomenon of Armenians converting to Islam to circumvent deportation orders, and focuses on the government's orders and decrees issued to confront this issue. Finally it briefly canvasses the hitherto neglected problem of prostitution by Armenian women as a strategy for survival during the war.